Analisa Kualitas Layanan Jaringan Internet Pada Wireless Lan Menggunakan Metode Qos (Quality Of Service) - Tangahu, Rizqi Adiputera; Andi Bode; Sunarto Taliki (Teknik Informatika Fakultas Ilmu Komputer Universitas Ichsan Gorontalo, 2024)
Abstract- The development of the Internet network is now very rapid. The Internet is a source of information that people mostly use to find information they need. It is not only used in big cities but also remote villages. The internet network must have a high access network speed to attract many users, whether or not in public facilities such as terminals or city parks. In other words, the internet network can make a big contribution to society. Currently, the internet has become a trending need, starting from the world of business, education, government, entertainment, and others. Kedai Mako is a coffee shop that uses the internet network as a means to make customers feel at home apart from its delicious coffee. Through internet networks, customers enjoy their coffee while playing games or social media without using their data quota. Kedai Mako customers using the internet network usually only know whether or nonot t the network is good by measuring the network speed via YouTube or online games. Yet, Internet users do not know whether or not the quality of the internet service they receive is good. It has not implemented QoS or measured network quality using QoS. The internet network at Kedai Mako often goes down, making customers uncomfortable with the internet network at Kedai Mako. Therefore, this research manages to analyze the internet network at Kedai Mako, and the results of the analysis can be used as recommendations for the physical implementation of the internet network hoped to be able to support the addition of other supporting services in the future. Based on the results of Quality of Service measurements in 5 experiments, the average value for the Throughput index obtained is 3,4 in the Very Good category, the index value for Packet Loss gained is 3.6 in the Very Good category, the index value for Delay analyzed is 4 in the Very Good category, and the Jitter index value indicates 3, in the Good category. The average index value for Kedai Mako is 3.5 in the Good category. Keywords: QoS, Wireshark, WLAN, Throughput, Packet Loss, Delay, Jitter